A systematic review on virtual reality technology for ancient ceramic restoration - Ming, Yue; Che Me, Rosalam; Chen, Jue Kun; Rahmat, Rahmita Wirza O. K. (Multidisciplinary Digital Publishing Institute, 2023)
The protection of intangible cultural heritage has received much attention, among which the “ancient ceramic restoration technique” was included in The National List of Intangible Cultural Heritage of China (the fourth batch) in 2014. In preserving and restoring ancient ceramics, virtual reality (VR) technology has been widely applied, as it provides a new way to showcase the appearance and structure of ancient ceramics in a VR environment. This paper provides a systematic review of the application of VR reality technology in the conservation and restoration of ancient ceramics. The methodology comprises four steps: research problem formulation, literature search, study selection and data extraction. A total of 30 articles out of 1479 peer-reviewed database articles from six databases (Web of Science, SpringerLink, IEEE Xplore, Scopus, CNKI, Google Scholar) were extracted and screened, which covers the application of VR technology or VR-based devices in ceramic conservation. It has been found that the existing VR application on ceramic restoration is hardly systematic or user-oriented. Thus, we develop a VR-based Platform on ceramic restoration utilized with Unity and 3DS Max, ensuring authenticity, minimal intervention, and promising reversible repair within the VR environment. The findings show that VR technology applied to ancient ceramic restoration has contributed to the learning efficiency and learning willingness of users.